Exploring Key Elements for Achieving Intergenerational Family Business Succession in the Chinese Context - Wei, Yuxin (International Journal of Social Sciences and Public Administration, 2024)
In the rapidly evolving Chinese economy, family-owned businesses, integral to the nation's GDP and innovation, face a significant challenge with an impending wave of intergenerational succession. With over 5.5 million such businesses, less than 20% have identified successors, and only 6% have established succession plans. This study examines intergenerational succession in these businesses, applying Handler's (1989) satisfaction and effectiveness framework, alongside Pyromalis et al. (2006)'s model. The research, conducted through interviews with second-generation owners, aims to uncover factors influencing succession satisfaction and effectiveness. Key findings highlight the unique impact of Chinese cultural values on the succession process. Unlike expectations, the reluctance of incumbents to relinquish control isn't a source of frustration for successors, reflecting the cultural emphasis on respect and deference to elders. The study broadens its scope beyond family dynamics to stakeholder relationships, acknowledging their importance in succession. This research merges theoretical and empirical analyses, adapting a Greek-tested model to the Chinese context, thus enhancing its global relevance. It provides insights into Chinese family business succession, shaped by cultural norms, and demonstrates the versatility of Western models in diverse cultural landscapes, enriching the understanding of global family business succession.